Effect of Rotational Speed on Hardness Value and Area of Vertical Bar-Plate Rotary Friction Weld Joint - Yohanes Yohanes; Meipen Meipen (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2022)
This study aims to determine the effect of rotational speed on the weld joint area and the hardness value of vertical bar-plate friction welding on dissimilar materials. Several testing methods were carried out, namely liquid penetrant, macro-observations, micro-observations and hardness test to investigation the welding results. The results of the liquid penetrant test have no effect on the welding specimens. Based on macro-observations was revealed a large enough cavity at a speed of 2.484 rpm with a cavity length of 4.76 mm, then getting smaller at a speed of 2.613 rpm with a cavity length of 2.63 mm. Then, at a speed of 4.335 rpm, no cavities were found. The micro-observation was a change in the microstructure, where in the weld metal area produces fine grains that affect the hardness value. The hardness value increases as it approaches the weld area. The highest hardness value at a speed of 4.335 rpm with a hardness value of 148.10 VHN, while the lowest hardness at a rotational speed of 2.484 rpm has a hardness value of 140.44 VHN.